2007
DOI: 10.1103/physrevb.75.212405
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic quantum critical point in URhGe doped with Ru

Abstract: We have investigated the thermal, transport and magnetic properties of URh$_{1-x}$Ru$_x$Ge alloys near the critical concentration $x_{cr} = 0.38$ for the suppression of ferromagnetic order. The Curie temperature vanishes linearly with $x$ and the ordered moment $m_0$ is suppressed in a continuous way. At $x_{cr}$ the specific heat varies as $c \sim TlnT$, the $\gamma$-value $c/T|_{0.5K}$ is maximum and the temperature exponent of the resistivity $\rho \sim T^n$ attains a minimum value $n=1.2$. These observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…The observed value of n, lower than 2 suggests the presence of non-Fermi liquid behaviour and is in good agreement with the previous results reported in [3]. In the theoretical models for the spin fluctuations and the local magnetic moments scenarios of FQCP Moriya and Millis and Hertz [7] have predicted n = 5/3.…”
Section: Results and Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The observed value of n, lower than 2 suggests the presence of non-Fermi liquid behaviour and is in good agreement with the previous results reported in [3]. In the theoretical models for the spin fluctuations and the local magnetic moments scenarios of FQCP Moriya and Millis and Hertz [7] have predicted n = 5/3.…”
Section: Results and Analysissupporting
confidence: 80%
“…Among these compounds URhGe, crystallising in an orthorhombic structure, seems to be very appealing due to the coexistence of ferromagnetic ground state (T C = 9.5 K) and superconductivity (T sc = 0.25 K) under ambient pressure [2]. Ru-doping experiments conducted on URh 1−x Ru x Ge system have shown that magnetic order vanishes at URh 0.62 Ru 0.38 Ge composition [3,4]. Non-Fermi liquid behaviour was found in specific heat and resistivity behaviour, and conception of ferromagnetic quantum critical point (FQCP) at this particular composition was proposed [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was motivated by the possibility to attain a ferromagnetic quantum critical point in URhGe by doping. Indeed in the URh 1-x Ru x Ge series T C (x) → 0 for x = 0.38 [13]. Notice, in the literature it was initially reported that UCoGe has a paramagnetic ground state [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…The ordered magnetic moment, m 0 , amounts to 0.20 µ B /U-atom (powder averaged value) [1,11,12] and the magnetic entropy, S mag , calculated by integrating the 5f electron specific heat ∫C 5f /TdT up to a temperature of approximately 1.5×T C amounts to 0.46×Rln2 (here R is the gas constant) [12,13]. This, together with the small ratio m 0 /p eff ~ 0.1 (the effective moment p eff ~ 1.7 µ B /U-atom [11,12]) confirms the itinerant nature of the ferromagnetic state.…”
Section: Introductionmentioning
confidence: 99%